Pengenalan Akuntansi Forensik dan Literasi Anti Fraud bagi Generasi Z Kota Serang - Arianto, Bambang; Suningrat (Rahmatan Lil 'Alamin Journal of Community Services, 2024)
This community service activity aims to strengthen the understanding of the importance of forensic accounting and anti-fraud literacy for generation Z. Forensic accounting is a scheme that can be developed as a preventive, detective and persuasive strategy through the application of investigative audit procedures with a litigation nature aimed at producing various findings and evidence, so that they can be used in the decision-making process in court. Understanding forensic accounting and anti-fraud literacy is very important for the lazy generation because it will form anti-fraud integrity. Strengthening forensic accounting literacy and anti-fraud literacy is very necessary so that the lazy generation can understand the triggering factors, and effective internal control strategies to mitigate the risk of fraud in the financial sector. This community service was carried out on 4th October, 2024 at SMK Negeri 7 Serang City, by providing training and assistance on the introduction of forensic accounting and anti-fraud literacy for generation Z in Serang City. In this training, various knowledge and education have been provided in the form of basic concepts of forensic accounting, fraud theory, forensic audits, investigative audits and stages of anti-fraud literacy for the lazy generation. The success of this community service activity is known to generation Z, who have been able to recognize, understand and implement the basic concepts of forensic accounting and anti-fraud literacy.